Pembelajaran Berbasis Inkubator Bisnis (Business Incubator Learnung/ BIBL) untuk Mengembangkan Jiwa Kewirausahaan - Eny Endah Pujiastuti (Jurnal Paradigma, 2011)
This applied research is Business incubator based learning (BIBL) to develop student entrepreneurial of Business Administration. The aim of this applied research is to develop entrepreneurship skill of student at Business Administration Department have entrepreneurship skill and create job opportunities.The sample of this experimental research is student of Business Administration Department of UPN “veteran” Yogyakarta. Using business incubators-based learning (BIBL) method, we found that the method learning is useful to cultivate entrepreneurship courage. The BIBL is applicable to other courses that use student-centered learning.